Gender, rainfall endowment, and farmers’ heterogeneity in wheat trait preference in Ethiopia - Gartaula, Hom Nath; Gebremariam, Gebrelibanos; Jaleta, Moti (2023)
Paper presented at the 7th African Conference of Agricultural Economics, 18-21 September 2021, Durban, South Africa. More information on the conference can be found here: https://www.acae2023.org/